EFFECT OF PEER TEACHING AND DISCUSSION METHODS ON SENIOR SECONDARY SCHOOL STUDENTS’ ACADEMIC ACHIEVEMENT IN BIOLOGY - Enebechi, Regina Ijeamasi (Top Educational Review Journal (TERJ), 2023)
The study investigated the effect of peer teaching and discussion method on secondary school students’ academic achievement in Biology in Enugu North Local Government Area of Enugu State. The study employed a quasi-experimental 2 x 2 factorial research design which helped the researcher to determine the main effects of two treatments in one single experiment., specifically the Pre-test, Post-test, Non-equivalent control group design was used. Four research questions were formulated to guide the study. The population size was 1780 SS II students and the sample size of 122 (52 males and 71 females) students. The main instruments for the study was Biology Achievement Test (BAT) and the students annual result for SS I. BAT consist objectives and essay sections, the reliability of the objective items was established using Kudder-Richardson formula 20 (K-R 20) and an index of 0.85 was obtained while interrater consistency of the essay items was 0.87 using Kendell. Mean and Standard deviation was used to answer the research questions. The results indicated that there was a significant difference in the mean achievement scores of students taught biology with peer-teaching method than those taught using discussion method with those taught using peer teaching method having a higher mean gain. The high ability students outperformed their medium and low ability students. This shows that student ability levels has effects on their academic achievement in biology There was no statistically significant difference in the mean achievement scores of male and female students. There was no statistically significant interaction effect of methods and gender on students’ achievement in biology. It was recommended among others that government agency whose responsibility is to design and revise the curriculum for secondary schools should incorporate the use of peer teaching method in teaching the students.